2013
DOI: 10.1161/hypertensionaha.113.01039
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness From Monitoring of Timing of Korotkoff Sounds Predicts the Occurrence of Cardiovascular Events Independently of Left Ventricular Mass in Hypertensive Patients

Abstract: Markers of subclinical target organ damage increase cardiovascular risk prediction beyond traditional risk factors. Arterial stiffness (AS) is one of these markers. 1 The predictive value for future cardiovascular events (CVEs) has been demonstrated for the carotido-femoral pulse wave velocity (PWV) in patients with renal failure, 2 in hypertensives, 3 and in the general population, 4 as well as from ambulatory measurement of the timing of Korotkoff sounds (QKD) in hypertensives. 5 The predictive value of AS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
2
15
0
2
Order By: Relevance
“…9 Because most of the pioneering epidemiological studies used the cfPWV method, novel devices using a different method for determining arterial stiffness should also demonstrate that the stiffness parameter which they measure has an independent predictive value for CV events. This is what has been adequately done by Gosse et al 7 in the article published in the present issue of Hypertension. Indeed, novel devices measuring a novel stiffness parameter cannot claim a predictive value for CV events simply from data showing a significant correlation between the novel parameter and cfPWV obtained during a cross-sectional validation study.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…9 Because most of the pioneering epidemiological studies used the cfPWV method, novel devices using a different method for determining arterial stiffness should also demonstrate that the stiffness parameter which they measure has an independent predictive value for CV events. This is what has been adequately done by Gosse et al 7 in the article published in the present issue of Hypertension. Indeed, novel devices measuring a novel stiffness parameter cannot claim a predictive value for CV events simply from data showing a significant correlation between the novel parameter and cfPWV obtained during a cross-sectional validation study.…”
supporting
confidence: 77%
“…The article by Gosse et al 7 published in the present issue of Hypertension provides an important contribution with regard to the predictive value of arterial stiffness for CV events for ≥4 reasons. First, the authors reported that arterial stiffness, measured in a population of 793 patients with hypertension with a mean follow-up of 97 months, was independently related to all CV events, major CV events, and total mortality.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Elle constitue également la première étude a utilisé le Popmètre comme outil de mesure de la RA chez des malades sclérodermiques. Les études antérieures étaient plutôt basées sur la mesure de l'intervalle QKd (temps qui sépare le complexe QRS de l'ECG de l'apparition du dernier bruit de Korotkoff perçu au niveau de l'artère humérale lors de la mesure de la tension artérielle [7]. Le Popmètre est une nouvelle méthode ambulatoire de mesure de la RA qui est objective, rapide, non invasive et surtout reproductible [8].…”
Section: Discussionunclassified